IDeS (Industrial Design Structure) Method Applied to the Automotive Design Framework: Two Sports Cars with Shared Platform - Leonardo Frizziero; Christian Leon-Cardenas; Gabriele Colasurdo; Alessandro Vicaretti; Alfredo Liverani (Inventions, 2022)
The present study was set to validate two different suburban-type sportscar bodies with shared common underpinnings. The chosen method to develop this project was the Industrial Design Structure (IDeS), which characterizes the ability to use the different innovative techniques known within the industrial field, across the whole organization. This method is embodied by following a series of structured analysis tools, such as QFD (Quality Function Deployment), Benchmarking (BM), Top-Flop analysis (TFA), Stylistic Design Engineering (SDE), Prototyping, Testing, Budgeting and Planning. This project aims to study the present-day car market and to foresee deployment in the near future. This attempt was confirmed by delivering the complete styling and technical feasibility characteristics of two different sports cars, obtained by the IDeS methodology. This approach of embodying design together with phases of product development would provide a better engineered, target-oriented product, that uses state-of-the-art style and CAD environments to reduce product development time and, hence, overall Time to Market (TTM).